Glycerine-CeCl3·7H2O: An Efficient Recyclable Reaction Medium for the Synthesis of Hantzsch Pyridines - Venkat Narsaiah, A.; Nagaiah, B. (Asian Journal of Chemistry, 2010)
1,4-Dihydropyridine synthesis has been carried out using glycerine-CeCl3·7H2O as a recyclable reaction medium. A variety of aldehydes undergo smooth condensation reaction with b-ketoester and ammonium acetate to afford the corresponding 1,4-dihydro pyridines in one-pot reaction in excellent yields.